Perolehan, Penyusutan, dan Penyajian Aset Tetap Berwujud dalam Laporan Keuangan pada PT Buana Internusa Logistik - Vetty Stevany (Akuntansi, 2022)
This study aims to analyze the acquisition, depreciation, and presentation of tangible fixed assets in the financial statements of PT Buana Internusa Logistik. The acquisition of fixed assets, including purchases, grants, and asset construction, as well as the company's depreciation practices, forms a critical part of financial reporting that impacts asset values and company profits. The research method employed is a descriptive approach with qualitative analysis, based on data collected through documentation studies of the company's financial statements. The findings indicate that PT Buana Internusa Logistik has managed the acquisition and depreciation of fixed assets in compliance with applicable accounting standards, although certain challenges in asset classification were identified, potentially affecting the accuracy of financial statement presentation. The implications of this study underscore the importance of a solid understanding of tangible fixed asset management to enhance the transparency and accuracy of corporate financial reporting, as well as ensuring that depreciation processes are carried out consistently in accordance with prevailing regulations.